A entrevista no documentário - Wainer, Julio (2014)
The objective of this research is to investigate how interviews are inserted into documentaries. To this end, a broad sampling of audiovisual shows identified in the field of documentaries (Brazilian, American and European short and feature-length documentaries; works of nonfiction identified as independent videos and Brazilian popular videos; audiovisual works produced by students) was mapped to determine how interviews are inserted into documentaries. An analysis was made of the authors‟ choices regarding the choice of sites, interview situation, cinematography, editing, and also how the interview is conducted by the interviewer, whom we see as the professional who appears most frequently in the end result. A categorization of the interviewees is proposed according to their roles in the film ( character, expert, vox-pop , etc.). This mapping highlights not only procedures that are repeated in the films, consolidating diffuse knowledge about interviews in documentaries, but also unique and singular moments that reveal an original solution or a more marked authorial vein on the part of the audiovisual author. The procedures were analyzed in the light of different trends in documentary literature, from the most normative theorists (Alan Rosenthal, Michael Rabiger) to theoretical-analytical authors (Jean-Louis Comolli, Bill Nichols). Among Brazilians, we highlight Fernão Pessoa Ramos and Jean-Claude Bernardet. Special attention focused on the work of cinematographer Eduardo Coutinho, in view of his deepening of the question of the interview in the documentary and of the diversity of available sources and process documentation (publications by Consuelo Lins and Eduardo Ohata, among others). With this research, we seek to identify how the execution and insertion of the interview characterize the uniqueness of the documentary, and how they indicate agglutinative currents and trends